Biogenic production and characterization of SeNPs (selenium nanoparticles) utilizing aqueous fruit extract of Morus alba and assessment of their biological potentialities - Tijo Cherian; Teena Merlin; Karthika Rajendran; Jacob Thomas (Results in Surfaces and Interfaces)
Plant-mediated methods of synthesizing nanoparticles have piqued the fascination due to their economical, rapidity, and environmental biocompatibility. Metal/metal oxide-based nanoparticles have long been a major attraction of researchers around the globe in various applications intersecting the various domains of science. The nanoparticles of silver, gold, zinc oxide, copper, copper oxide have been surveyed extensively with copious documentations of synthetic, applicative and practical insights. Selenium, as a precursor has remained largely been underexplored and under prospected. There is few research on the green synthesis of selenium nanoparticles (SeNPs) because of limitations with the process's intricacy, unpredictability, and possibility for low purity. Although green synthesis is virtuous for the environment, it can be time-consuming, location-dependent, and subject to change based on the plant source. Furthermore, the precise method and effects of each plant are not entirely understood, even though reducing agents in plant extracts can transform metal ions into nanoparticles. The current work presented a first-hand employment of aqueous fruit extracts of Morus alba in the biological synthesis of selenium nanoparticles (SeNPs). The characterization studies [UV–Vis (ultraviolet–visible), Raman spectroscopy, TEM (transmission electron microscopy), SEM (scanning electron microscopy), FTIR (Fourier transform infrared spectroscopy), zeta potential] authenticated and established the fabrication of SeNPs. The GC-MS (Gas chromatography-Mass spectrometry) analysis reported the presence of a multitude of organic compounds; well authenticated for the novel pharmaceutical candidates by molecular docking studies. The synthesized SeNPs reported promising and exceptional activities in various biological experimental evaluations. Also, the growing manufacturing of environmentally friendly nanoparticles necessitates research on their safety for biological systems and environment. The findings demonstrated that the SeNPs might, in a dose-dependent way, lower the end-points of photosensitive pigments and biomass of Chlorella vulgaris. The dye reaction dynamics was found to be outstandingly high following pseudo-first order kinetics with a 95–96 % degradation rate, implying SeNPs as favorable candidates for catalysis.